Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario, 2019)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (Chaire de recherche de l’Université d’Ottawa et de l’Institut du Savoir Montfort sur la santé des francophones de l’Ontario, 2019)

The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (University of Ottawa & Institut du Savoir Montfort, 2019)
fs-ref-orig: Bouchard, L., Colman, I., Dubois, A., & Sucha, E. (2019). The mental health of Francophone minorities: An overview from the Canadian community health survey-Mental health 2012. University of Ottawa & Institut du Savoir Montfort. fs-code-orig: Bouchard-2019e

La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012 - Bouchard, Louise; Colman, Ian; Dubois, Alejandra; Sucha, Ewa (Université d’Ottawa et Institut du Savoir Montfort, 2019)
Nombre de pages: 94 fs-ref-orig: Bouchard, L., Colman, I., Dubois, A. et Sucha, E. (2019). La santé mentale des francophones en situation minoritaire au Canada : un portrait tiré de l’Enquête sur la santé dans les collectivités canadiennes-Santé mentale 2012. Université d’Ottawa et Institut du Savoir Montfort. fs-code-orig: Bouchard-2019a

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d’Ottawa et Institut du Savoir Montfort, 2019)
Nombre de pages: 24

Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec - Sucha, Ewa; Silva, Erika; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)
L’objectif de ce rapport est d’examiner la mortalité selon la situation socioéconomique des francophones et des anglophones du Canada vivant à l’extérieur du Québec et d’évaluer les effets indépendants du niveau de scolarité, du niveau de compétence professionnelle et du quintile de revenu sur la mortalité selon le sexe et le groupe linguistique. Il s’agit d’une analyse secondaire des données couplées de l’étude canadienne de suivi de la mortalité et du cancer selon le recensement, 1991 à 2006 créé par Statistique Canada (Wilkins et al., 2008). Environ 2,7 millions de personnes (15 % de la population du recensement de 1991) âgées de 25 ans ou plus (excluant les pensionnaires d’établissements institutionnels) ont été suivies pour la mortalité (1991 à 2006), le cancer (1969 à 2006) et le lieu de résidence annuel (1990 à 2007). Nous avons retiré de la cohorte originale les résidents du Québec (697 850), les personnes bilingues parlant le français et l’anglais (5 980) et les personnes ne parlant ni l’une ni l’autre des langues officielles (22 360). L’étude est basée sur un échantillon de 1 896 920 anglophones (946 875 hommes; 950 040 femmes) et 105 710 francophones (52 045 hommes; 53 675 femmes) vivant à l’extérieur du Québec. Analyses statistiques: Des mesures descriptives ont été utilisées et sont résumées en tableaux sous forme de pourcentages. Les caractéristiques de la population ont été comparées entre les groupes linguistiques pour la population totale et la population décédée, et pour les hommes et les femmes, séparément. Des tests de Chi-carré ont été utilisés pour comparer la distribution proportionnelle des décès dans toutes les catégories entre les francophones et les anglophones pour chaque variable. En outre, les taux de mortalité normalisés (TMNA), l'espérance de vie à 25 ans et les probabilités de survie jusqu'à l'âge de 75 ans ont été calculés en fonction de facteurs socio-économiques clés tels que le niveau de scolarité, le niveau de compétence professionnelle et la suffisance des revenus pour les hommes et les femmes séparément dans chaque communauté linguistique. Finalement, pour mesurer l’impact de ces facteurs sur la mortalité toutes causes confondues et la mortalité par cause spécifique de chacun des groupes susmentionnés, le modèle de régression à risques proportionnels de Cox a été utilisé. Les catégories de référence ont été choisies pour mettre en évidence l'effet du faible statut socio-économique des répondants sur la mortalité par rapport aux personnes qui sont dans une meilleure situation socio-économique, c’est-à-dire celles qui ont des niveaux de scolarité et de revenus plus élevés, et une profession plus qualifiée.
fs-ref-orig: Sucha, E., SIlva, E., Batista, R. et Bouchard, L. (2014). Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec. Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa. fs-code-orig: Sucha-2014b

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)
fs-ref-orig: Bouchard, L., Sedigh, G., Sucha, E. et van Kemenade, S. (2014). Les hommes et les femmes francophones en Ontario : un portrait de leur santé. Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa. fs-code-orig: Bouchard-2014e

The health of Francophone men and women in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario & University of Ottawa, 2014)

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)
fs-ref-orig: Bouchard, L., Sedigh, G., Sucha, E., & van Kemenade, S. (2014). Francophone men and women in Ontario: A health portrait. Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa. fs-code-orig: Bouchard-2014f

Précarité des populations francophones âgées vivant en situation linguistique minoritaire - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Sedigh, Golnaz; Silva, Erika. E.; Sucha, Ewa (Minorités linguistiques et société, 2015)
Le vieillissement des populations s’est considérablement accentué ces dernières décennies et ce plus particulièrement pour la population francophone vivant en situation linguistique minoritaire au Canada. Nos analyses secondaires de l’Enquête sur la santé des collectivités canadiennes (ESCC) révèlent qu’une grande proportion d’aînés francophones n’a pas de diplôme d’études secondaires et se situe dans le quintile de revenu le plus faible. Des analyses multidimensionnelles des données montrent que les déterminants de la pauvreté tels que le revenu et l’éducation exercent une influence sur la pauvreté des personnes âgées, mais que la langue et l’appartenance à la minorité francophone y contribuent de façon spécifique, ce qui constitue une donnée nouvelle. Mots-clés : vieillissement, minorités linguistiques, personnes âgées, pauvreté, déterminants sociaux de santé

Ascertaining the Francophone population in Ontario: validating the language variable in health data - Batista, Ricardo; Hsu, Amy T.; Bouchard, Louise; Reaume, Michael; Rhodes, Emily; Sucha, Ewa; Guerin, Eva; Prud'homme, Denis; Manuel, Douglas G.; Tanuseputro, Peter (BMC Medical Research Methodology, 2024)
Abstract Background Language barriers can impact health care and outcomes. Valid and reliable language data is central to studying health inequalities in linguistic minorities. In Canada, language variables are available in administrative health databases; however, the validity of these variables has not been studied. This study assessed concordance between language variables from administrative health databases and language variables from the Canadian Community Health Survey (CCHS) to identify Francophones in Ontario.

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.

Impact of patient–family physician language concordance on healthcare utilisation and mortality: A retrospective cohort study of home care recipients in Ontario, Canada. - Reaume, Michael; Batista, Ricardo; Sucha, Ewa; Pugliese, Michael; Roberts, Rhiannon; Rhodes, Emily; Seale, Emily; Kendall, Claire. E.; Bjerre, Lise; Bouchard, Louise; Johnson, Sharon; Sood, Manish; et al. (BMJ Public Health, 2024)
Introduction As the world’s linguistic diversity continues to increase at an unprecedented rate, a growing proportion of patients will be at risk of experiencing language barriers in primary care settings. We sought to examine whether patient–family physician language concordance in a primary care setting is associated with lower rates of hospital-based healthcare utilisation and mortality. Methods We conducted a population-based retrospective cohort study of 497 227 home care recipients living in Ontario, Canada. Patient language was obtained from home care assessments while physician language was obtained from the College of Physicians and Surgeons of Ontario. We defined primary care as language concordant when patients and their rostered family physicians shared a mutually intelligible language, and we defined all other primary care as language discordant. The primary outcomes were Emergency Department (ED) visits, hospitalisations and death within 1 year of index home care assessment. Results Compared with non-English, non-French speakers who received language-discordant primary care, those who received language-concordant primary care experienced fewer ED visits (53.1% vs 57.5%; p<0.01), fewer hospitalisations (35.0% vs 37.6%; p<0.01) and less mortality (14.4% vs 16.6%; p<0.01) during the study period. In multivariable regression analyses, non-English, non-French speakers had lower risks of ED visits (adjusted hazard ratio [aHR] 0.91, 95% CI 0.88 to 0.94), hospitalisations (aHR 0.94, 95% CI 0.90 to 0.98) and death (aHR 0.87, 95% CI 0.82 to 0.93) when they received language-concordant primary care. For francophones, the risk of experiencing an ED visit, a hospitalisation or death was not impacted by the language of their family physician. Conclusions Patient–family physician language concordance is associated with a lower risk of adverse outcomes in non-English and non-French speakers. Optimising the delivery of language-concordant care could potentially result in significant decreases in the use of acute healthcare services and mortality at the population level.